Pengaruh Kepuasan Kerja Dan Beban Kerja Terhadap Kinerja Karyawan PT. Airmas Perkasa - Debby Sagita; Adrie Frans Assa (Ilmiah Manajemen Bisnis, 2019)
Abstract — This study aims to determine: (1) The effect of job satisfaction on the performance of employees of PT. Airmas Perkasa (2) Effect of workload on the performance of employees of PT. Airmas Perkasa. Analysis of data using IBM SPSS Statistics 24. The research method used in this study is a quantitative research method, with a probability sampling technique of 102 samples. Meanwhile, the analytical method used is multiple linear regression method. The results of t-test calculations show that: (1) Job satisfaction variables have a positive and signifcant effect on employee performance, because the value of t count (5.470) <t table (1.9840) and a signifcant value of 0.000 <0.05. (2) Workload variables have a negative and signifcant effect on employee performance, because the value of t count (2,913) <t table (1.9840) and signifcant value 0.004 <0.05 based on the results of calculations that have been described, it can be concluded that the variable job satisfaction has a positive effect and signifcant to the performance of employees of PT. Airmas Perkasa and workload variables have a negative and signifcant effect on the performance of employees of PT. Airmas Perkasa. Keywords—Research, Job Satisfaction, Workload, Employee